No one would listen : a true financial thriller - Markopolos, Harry (Finance professional collection, 2010)
Harry Markopolos and his team of financial sleuths discuss first-hand how they cracked the Madoff Ponzi scheme. No One Would Listen is the exclusive story of the Harry Markopolos-lead investigation into Bernie Madoff and his 65 billion Ponzi scheme. While a lot has been written about Madoff's scam, few actually know how Markopolos and his team-affectionately called "The Fox Hounds" by Markopolos himself, uncovered what Madoff was doing years before this financial disaster reached its pinnacle. Unfortunately, no one listened, until the damage of the world's largest financial fraud eve.